Effect of hot air temperature and slice thickness on the drying kinetics and quality of Hami melon (Cantaloupe) slices - Tianying Sun; Ning Wang; Cuntang Wang; Jian Ren (Scientific Reports)
Abstract The effects of hot air temperature and slice thickness on the drying kinetics and quality of Hami melon slices (HMS) were studied. HMS (3 mm and 5 mm) were carried out in a forced convection drying oven at temperatures ranging from 60 ~ 90 °C. The increase in hot air temperature and the decrease in slice thickness led to shorter drying times and higher drying rates. The drying rate curves indicated that the drying process of HMS did not exhibit a constant drying rate period. In the drying kinetics modeling process, the Explinear model was suited for describing the drying curves with higher accuracy. According to Fick’s second law, the moisture effective diffusion coefficient of 3 mm and 5 mm HMS ranged from 4.72 ~ 15.96 × 10-11m2/s at temperatures of 60, 70, 80, and 90 °C. When the thickness of HMS were 3 mm and 5 mm, the activation energies were 30.13 and 43.75 kJ/mol, respectively. When dried at low temperatures, the color of HMS was closer to fresh Hami melon. With the increase of hot air temperature, the hardness of HMS decreases and the rehydration increases. When the thickness of the HMS decreases, the hardness of the slices decreases and the rehydration increases.